Farming tambaqui (Colossoma macropomum) in static clear water versus a biofloc system with or without Bacillus subtilis supplementation - Santos, Driely Kathriny Monteiro dos; Kojima, Juliana Tomomi; Santana, Thiago Macedo; Castro, Diogo Pereira de; Serra, Paula Taquita; Dantas, Naiara Silva Menezes; Fonseca, Flávio Augusto Leão da; Mariúba, Luís André Morais; Gonçalves, Ligia Uribe (Aquaculture International, 2020)
The use of probiotics can beneficially improve the water quality in the biofloc technology (BFT) system consequently enhancing the fish performance. This study focused on the effect of Bacillus subtilis on a clear water static system compared to the BFT system on the productive performance, proximate body composition, and diversity of intestinal bacterial communities of tambaqui (Colossoma macropomum) juveniles submitted to four treatments: clear water static system with (CW + BS) or without (CW) B. subtilis and BFT with (BFT + BS) or without (BFT) B. subtilis. For the study, 20 juveniles (five replicates) per treatment were used for 60 days. For the B. subtilis treatments, water was inoculated at weekly intervals with a 4 × 108-cell mL−1 culture suspension. Results revealed that regardless of B. subtilis supplementation, fish reared in BFT displayed better zootechnical performance than those in CW—weight gain (BFT 33.57 ± 4.08 g; CW 19.97 ± 5.42 g), protein efficiency (BFT 0.16 ± 0.02; CW 0.11 ± 0.02), feed conversion ratio (BFT 0.71 ± 0.08; CW 0.84 ± 0.40), and relative growth rate (BFT 1.52 ± 0.12; CW 1.06 ± 0.15)—which suggests that biofloc consumption was 31.9% crude protein. Moreover, fish reared in BFT + BS had a higher condition factor (2.30 ± 0.09). In conclusion, BFT is regarded as a promising system to save water, decrease aquaculture effluents, and promote tambaqui farming. Although B. subtilis is a common bacterium found in tambaqui gut, its supplementation in the BFT system improved the fish condition factor. © 2020, Springer Nature Switzerland AG.